Correlation of joint roughness coefficient and permeability of a fracture. (January 2019) - Rezaei Niya, S.M.; Selvadurai, A.P.S.
Abstract: This paper uses a new modeling approach to study fluid transport in an open fracture, which relies on data derived from scanned surfaces of fractures and considers surface variations and velocity Laplacians in two orthogonal directions and the bulk flow rotation. The model predictions are verified against the results for incompressible flow modeling obtained using the procedures available in COMSOL™ multiphysics. The model examines the relationship between the joint roughness coefficient (JRC) and permeability of a fracture. A new method is presented to reproduce the surfaces of the fracture using both JRC and the fractal dimension. The JRC-permeability correlation is analyzed in exactly mated surfaces, surfaces that have undergone translations in their plane and independent surfaces to highlight the importance of the relative displacement of fracture surfaces in fluid transport analysis. A shifting threshold from which two translated surfaces can be considered independent is determined. It is shown that even a 62.5-micron translation for an aperture size of 0.1 mm has a noticeable effect on the permeability, which first decreases and then increases because of surface translation; the cubic law consistently underestimates the permeability for small apertures (< 0.1 mm) and moderate to high JRCs (> 10) for independent surfaces. The effect of sample size and contact area ratios are also discussed. The presented model is a first step towards developing a computationally efficient, reasonably accurate model for statistical analysis of the fluid transport properties of a network of stressed fractures.